Prevalence of H. pylori Infection in Relatives of Peruvian Patients with Gastric Cancer - Castillo, Miluska (2021)
bjective: The aim of this study was to determine the relationship between Helicobacter pylori (H. pylori) infection in relatives and patients with gastric cancer (GC). Methods: H. pylori infection was evaluated by the breath urease test in 171 relatives and by qPCR technique in gastric tissue of 61 patients (n=45 for GC and n=16 for non-GC). Results: There were included 137 relatives of GC patients and 34 of non-GC. The median age of the relatives of patients with a gastric tissue sample was 39 years (10-86). Infection was found in 60.2% (n=103) relatives. There were no higher H. pylori infection rates in relatives of patients with gastric cancer (62% vs 62.9%, p=0.33), H. pylori infection (60% vs 60%, p=0.96), or metaplasia (58.8% vs 61.8%, p=0.71). Conclusion: The prevalence of infection in relatives of GC patients is high in our population but not associated with H. pylori presence in the paired case